Power losses reduction analysis in Mae sariang microgrid system - Jetsada Kantiyawong (2018)
© 2017 IEEE. This paper presents research power losses analysis in Mae Sariang microgrid system (MGs) by installing distribution generators (DGs). The studied case is located in Mae Sariang district, Mae Hong Son province which is a remote area. The main grid cannot supply sufficient active power to high consumption load in the system because there are high power losses occur in 22 kV transmission lines. This paper solves this problem with appropriated DGs selecting. There are 4 types of DGs such as diesel generator, solar system, hydro generator and battery storage in Mae Sariang MGs. This paper finds which type and number of DGs will supply minimum power losses while the system is in the grid-connected mode or island mode. System analysis used the DigSILENT Power Factory software. Our research was carried out in the 22kV distribution system of the Provincial Electricity Authority of Thailand (PEA).